Recent Advances in PROTAC Technology Toward New Therapeutic Modalities - Yokoo, Hidetomo; Naganuma, Miyako; Oba, Makoto; Demizu, Yosuke (Chemistry & biodiversity, 2022)
Proteolysis targeting chimeras (PROTACs) have emerged as a powerful technology for the degradation of disease‐related proteins by the hijacking of the endogenous ubiquitin‐proteasome system. A multitude of bifunctional PROTACs have been developed using small‐molecule ligands; one ligand binds to the target protein of interest and one ligand binds to an E3 ligase. The characteristics of those PROTACs vary, including their reversible or irreversible covalent binding to the target protein, their binding to orthosteric and allosteric sites, their agonist or antagonist activity, and their use of multiple ligands. In addition, oligopeptides and nucleotides have recently been used as alternative targeting ligands. The properties of PROTACs, such as selectivity, delivery and sensitivity to drug resistance, can be improved through the use of a variety of targeting ligand modalities. This minireview introduces the mechanisms and behavior of small‐molecule based PROTACs as well as targeted proteolysis techniques using peptides and nucleic acids as targeting ligands.